The Impact of Organizational Support on Nurse Work Performance Mediated by Mental Health During the Covid-19 Pandemic - Aisyah Nabila Azuraa; Rusman Frendika; Hadi Susiarno; Nina Mariana (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
During the Covid-19 pandemic, a previous study has shown that organizational support increases mental health, mental health increase work performance, and organizational support increases work performance. However, there was still no study that identified the degree of mediation role of mental health in the relationship between organizational support and work performance; hence this study mainly aimed to investigate whether it was partial or full mediation. We conducted a cross-sectional, quantitative analytical study on nurses of the Covid-19 referral hospital in Jakarta. We used an adapted questionnaire on 127 nurses, validated and analyzed with path analysis. This study found that there was a significant effect of organizational support on work performance both directly and indirectly via mental health. It was proven that mental health mediates the relation of organizational support with work performance. The mediation that occurred was partial mediation. From this result, besides giving the best possible support, the hospital also needs to focus on nurses' and other health workers' mental health, as organizational support will affect work performance better when mental health is in a good state.